PANOPHTHALMITIS SECONDARY TO RETAINED INTRAOCULAR FOREIGN BODY , SETTING IN RURAL AREA: Poster Presentation - Case Report - Ophthalmologist - WAHYU ENDAH PRABAWATI (Majalah Oftalmologi Indonesia, 2023)
Introduction : IOFB can be serious and result in vison threatening complication. We report IOFB presenting with panophtalmitis secondary to delay in seeking medical attention and misdiagnosed in emergency ward by general practitioner. Case Illustration : A 40-years-old male presented with pain and outward bulging of his right eye with no light perception after trauma to his right eye by a small metallic object while working as electric grasscutter. He presented to our department 3 days following the incident. Systemically, he had a fever, headache and nausea. 2 days after incident, he visited to emergency ward but he was given eye drop only. On Slit lamp examination, corneal melting with keratinization and lacerated wound in cornea at 12 o'clock about 3 mm. Non-contrast CT showing a linear hyperdense foreign body in the right globe likely metal, measuring 3 mm x 4 mm was found. The patient was admitted ceftriaxone intravenous, twice daily. No light perception of visual acuity, ocular penetrating, persistence of the active inflammation, and risk of spread, a decision was made to eviscerate the eye. A metallic foreign body was found in eviscerated tissue. Discussion : Conclusion : Important to suspect foreign body in all cases ocular trauma. Detailed examination and imaging should be performed. Delay treatment from the time of injury, result in poor prognosis. Surgical treatment such as evisceration, should be informed to patient about the visual prognosis.